Literatur Review: Strategi Penanganan Pemukiman Kumuh di Kelurahan Batang Arau Kota Padang terkait Sanitasi dan Kesehatan Lingkungan - Fitrya Monica; Fadel Ikrar Jamika; Abdul Razak; Linda Handayuni; Elsa Yuniarti; Mhd. Fauzi (Fakultas Teknik, 2023)
AbstractSanitation and environmental health are complex problems facing Indonesia today. If these problems are not addressed immediately, this will certainly have an impact on sanitation and environmental health in the settlements themselves, such as the emergence of germs. So this literature review aims to describe the description and handling strategies of slums settlements in Batang Arau Village, Padang City regarding sanitation and environmental health. The method used is qualitative and literature review. The results of the study show that the settlements in Batang Arau Village, Padang City have mild, medium, and large slums sanitation categories. The environment street and drinking water supply are in the low category. The medium category includes buildings, waste water management, and solid waste management. While environmental drainage and fire protection are included in the large category. The handling strategy that can be taken to deal with these slums settlements are to carry out a socialization program in the form of the Kotaku Program, create an environment-based slums settlement concept, carry out a community empowerment/ human resources (HR) strategy, carry out sustainable slums management, and carry out area management plans settlement. If this strategy is carried out, it will reduce slum settlements in the PadangCity.Keywords: Batang Arau Village, environmental health, slums, sanitation, handling strategies